Gandhi and the Parable of the Prodigal Son - Damm, Alex (2021)
This essay seeks to emphasize the important bearing which multiple and quotidian, personal contexts have on the biblical exegesis of Mohandas K. Gandhi. The essay focuses on Gandhi’s interpretation of the parable of the Prodigal Son (Luke 15:11–32), asking in particular why Gandhi’s reading departs from the parable’s literal sense. While the most evident reason for Gandhi’s distinctive interpretation is his philosophy of satyagraha or non-violent resistance, there emerge behind this appeal, several more precise contexts that plausibly contributed to Gandhi conceiving of satyagraha as the parable’s interpretive key. These contexts included political exigencies that Gandhi faced in mid-1920; his relationship with his son Harilal; and the profile of one of his interlocutors, Sir Narayan Chandavarkar. This essay emphasizes the importance of such varied and personal contexts that merge to help shape Gandhi’s interpretation, and closes with implications for further study of biblical exegesis by Gandhi and more generally in the global south.
Keywords: Gandhi; Non-violence; Prodigal Son; Parables